Hubungan antara Minat Belajar dengan Kemampuan Reasoning Matematis Mahasiswa pada Mata Kuliah Geometri: Relationship between Interest in Learning and Student Mathematical Reasoning Ability in Geometry Courses - I Putu Ade Andre Payadnya; I Made Dharma Atmaja; Kadek Adi Wibawa (Emasains : Jurnal Edukasi Matematika dan Sains, 2019)
This research is a quantitative study with a correlation approach to determine whether or not there is a relationship between interest in learning and students' mathematical reasoning abilities in geometry. The subjects of this study were IA class students of Mathematics Education Study Program, Faculty of Teacher Training and Education, Mahasaraswati University Denpasar 2018/2019 academic year. Data was collected through questionnaire and documentation. Data were analyzed with the help of SPSS for Windows v.20 software. The results obtained from this study include: (1) learning interest of students with very interested categories = 62.5%, interested = 25%, and quite interested = 12.5%. (2) There is a positive and significant relationship between interest in learning mathematics with learning outcomes of mathematics with a value of rxy = 0.84 and a test result (2-tailed) of 0.027.